Wandlungen in der jugoslawischen Landwirtschaft - Kubiëna, Wolfgang (ERDKUNDE, 1955)
Since World War II the agricultural landscape of Yugoslavia has undergone a thorough change. Nevertheless, it must not be overlooked that the physical conditions as well as the past development are still clearly reflected in the present rural scene. During the first years after the war the governmental policy was first and foremost directed toward, industrialization, but after its detachment from the Eastern Bloc more interest was again devoted to agriculture. Today the amalgamation of holdings into collectives and co-operatives is completely voluntary and accordingly has reached different degrees in different regions. In this connection it should be noted that communal working of fields had been the rule for a long time in the south-eastern part of the country. Judgement must however be reserved until some later date as to whether the fragmentation of holdings which resulted from various measures of expropriation of estates will not in the long run have detrimental effects.